William Shakespeare - Dickins, Rosie; Illustrated by Unzner, Christa (London Usborne Publishing ltd, 2008)
William dreams of acting and writing plays. This ambition takes him from the quiet country town of Stratford to the great playhouses of London, where his talent takes the city by storm... The life of Britain's most famous playwright told for children ready to tackle longer and more complex books
Include Color Illustration and Index
Keywords: Shakespeare, William